Forty Years of Arctic: The Journal of the Arctic Institute of North America - Harrison, Roman; Hodgson, Gordon (ARCTIC, 1987)
When the Arctic Institute of North America was established in 1945 as a membership institution, it was understood that the membership expected the Institute to publish a journal. It appeared for the first time in 1948, as Arctic, The Journal of the Arctic Institute of North America, and has been published continuously for 40 years since then. It is now a leading academic journal publishing research papers from a variety of disciplines on a wide range of subjects dealing with the Arctic. Over the 40 years it published 40 volumes comprising 1231 research papers and other related material. The present study reports a content analysis of the 1231 papers revealing that trends over the last 40 years of research in the North were guided by the economic and academic pressures of the day for northern research. The bulk of papers in the 40 years involved three major areas: biological sciences, earth sciences and social sciences. The proportion of research papers in earth sciences showed a decline, accompanied by a strong growth in biological science papers and a modest growth in social science papers. Over the 40 years, subjects sited in the Canadian Arctic always dominated, with a steady growth from 23% of the total papers per volume to 42%. In particular, significant increases in the numbers of papers in the last 10 years came from resource-related work in the North, as well as from political, educational, cultural and sovereignty-related research. Research in the North leading to publication in Arctic was conducted largely by biologists and earth scientists. Canadian and American authors accounted for most of the papers, with the proportion being roughly equal. . Numbers of manuscripts received by Arctic increased steadily over the years . Acceptance rates declined slightly over the years to the present rate of 60%. .Key words: Arctic Institute of North America, Arctic, content analysis, trends, subject matter, location of study area, author’s discipline, author’s nationality Quand l'Institut arctique de l'Amérique ...